안구건조증 모델에서 미세조류의 완화 효과 - 김진우; 김이준; 김성진; 김진철 (한국식품과학회, 2023)
Dry eye is a disorder of the ocular surface that causes discomfort and fluctuating vision. This study aimed to investigate the protective effect of Nannochloropsis oceanica, Tetraselmis chuii, and Phaeodactylum tricornutum, microalgae, on the dry eye mouse model. Tear volume was significantly increased in the T. chuii and P. tricornutum treated group. Also, T. chuii and P. tricornutum ameliorated the damaged corneal surface and its structure. In addition, atrophied acinar cells in the lacrimal gland of mice were significantly recovered by T. chuii and P. tricornutum administration. Inflammatory cytokine expression levels were downregulated after microalgae treatment. Particularly, T. chuii improved tear volume, corneal epithelial thickness, atrophied acinar cells, and inflammatory cytokines level most excellently among the three microalgae. These results suggest that T. chuii could be applied as a functional food due to their therapeutic effects on the dry eye mouse model.